Legal Protection For Victims of Criminal Offense In The Perspective of Law Number 16 of 2011 on Legal Aid - Edi; Rospita Adelina Siregar (Universitas Muhammadiyah Palu, 2025)
This research discusses legal protection for victims of criminal acts according to Law Number 16 of 2011 concerning Legal Aid. Although legal aid is very important and needed for victims of criminal acts, its application is still limited, especially litigation legal aid for victims, which results in many victims of criminal acts not getting legal aid assistance. The provisions in Law Number 16 of 2011 limit the provision of litigation legal aid only to suspects, defendants, and convicts, resulting in victims being neglected. This research aims to explore efforts to provide legal aid for victims based on Law Number 16 of 2011 concerning Legal Aid and the importance of legal protection assistance for victims of criminal acts.